2018
DOI: 10.1093/jas/skx040
|View full text |Cite
|
Sign up to set email alerts
|

Effects of adding mannan oligosaccharides on digestibility and metabolism of nutrients, ruminal fermentation parameters, immunity, and antioxidant capacity of sheep1

Abstract: The purpose of this study was to investigate the effects of adding mannan-oligosaccharides (MOS) on the following parameters in sheep: digestibility and retention rate of nutrients, ruminal fermentation, immunity, and antioxidant capacity. Twelve healthy crossbred wethers (Suffolk ♂ × Small tail Han-yang ♀) with external ruminal fistula and similar body weights (28.04 ± 2.07 kg) were fed individually four treatments, three repeats of each treatment. The wethers diets were supplemental MOS at 0%, 1.2%, 1.6%, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 37 publications
2
24
1
2
Order By: Relevance
“…A previous study found that GOS significantly increased the DE of sheep fed with Italian ryegrass hay and concentrate (3:2, on a DM basis), but did not affect nitrogen digestion and retention [24]. Other researchers reported that MOS did not affect the apparent digestibility and retention rate of nutrients in cattle and sheep [4,10]; these findings are in accordance with that of Goiri et al [25], who pointed out that chitosan did not influence the nutrients’ apparent digestibility. However, another study indicated that MOS enhanced the health of the ruminal epithelium of sheep by reducing the thickness of the stratum corneum, and it might have increased the nutrients digestion [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study found that GOS significantly increased the DE of sheep fed with Italian ryegrass hay and concentrate (3:2, on a DM basis), but did not affect nitrogen digestion and retention [24]. Other researchers reported that MOS did not affect the apparent digestibility and retention rate of nutrients in cattle and sheep [4,10]; these findings are in accordance with that of Goiri et al [25], who pointed out that chitosan did not influence the nutrients’ apparent digestibility. However, another study indicated that MOS enhanced the health of the ruminal epithelium of sheep by reducing the thickness of the stratum corneum, and it might have increased the nutrients digestion [9].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, MOS bind to the mannose-specific lectin of Gram-negative pathogens that express Type-1 fimbriae (e.g., Escherichia coli ), resulting in their excretion from the intestine [7]. The limited research focusing on MOS in ruminants found that MOS improved the immunoglobulin G (IgG) concentration of lamb’s blood [8], enhanced the health of the ruminal epithelium of sheep [9], improved the colostrum quantity of cows [4], and increased the antioxidant capacity of sheep [10]. In previous study, β 1-4 galacto-oligosaccharides (GOS) reduced the CH 4 production in sheep [11]; however, very few scientists have studied the effect of MOS on the energy metabolism and gas emission of ruminants.…”
Section: Introductionmentioning
confidence: 99%
“…MOSs are the prebiotics widely used in food and animal feed to improve gastrointestinal health (Forsatkar et al 2017;Zheng et al 2018;Nguyen et al 2019). The endomannanases capable of catalysing the hydrolysis of b-1,4linked bonds among the mannan substrates are valuable enzyme resources for MOSs production (Chauhan et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…A forma mais eficiente de consegui-lo é através da gestão adequada dos programas de alimentação, o balanceamento correto da ração e, a utilização de aditivos alimentares que visam auxiliar o processo fermentativo no rúmen (Pinloche et al, 2013). Entre os aditivos alimentares mais importantes utilizados atualmente destacam-se os probióticos e prebioticos, por serem considerados compostos naturais, que além de melhorar o desempenho, têm um impacto positivo na saúde do indivíduo e no bem-estar dos animais (Hady et al, 2012;Mohammed et al, 2013;Broadway et al, 2015;Zheng et al, 2018;Diaz et al, 2018ab). Os probióticos como as culturas de levedura vivas como a Saccharomyces cerevisiae e prebióticos, particularmente os mananoligossacarídeos (MOS) são aditivos capazes de produzir uma variedade de respostas benéficas no hospedeiro.…”
Section: Probióticos: Leveduras Vivas Saccharomyces Cerevisiaeunclassified
“…Os prebióticos são definidos como ingredientes alimentares, constituídos basicamente por polissacarídeos e oligossacarídeos, que não são digeridos na porção proximal do trato gastrintestinal, principalmente de animais monogástricos (Rai et al, 2013). Nos ruminantes, os prebióticos estimulam o crescimento de diversas bactérias ruminais e intestinais benéficas, cujos metabólitos atuam melhorando o aproveitamento e a digestibilidade dos alimentos (Uyeno et al, 2015;Zheng et al 2018). Além disso, outros efeitos benéficos dos prebióticos, como agentes que atuam contra tumores, anti-inflamatórios, anti-mutagênicos, hipocolesterolêmico, hipoglicêmico e proteção contra infecções vem sendo estudados e comprovados (Kim et al, 2006).…”
Section: Prebiótico: Mananoligossacarídeos (Mos)unclassified